RATIONAL COMBINATIONS IN HYPERTENSION TREATMENT - V. I. Podzolkov; A. I. Tarzimanova (Рациональная фармакотерапия в кардиологии)
Influence of the combined antihypertensive therapy, including combination of ACE inhibitors and dihydropyridine calcium channel blocker (DCCB), on frequency of cardiovascular events is studied in many trails. Advantages of the combination of ACE inhibitor and DCCB which is one of the most rational are discussed. Both components are vasodilators and have synergistic mode of action in arterial hypertension. Combination of ACE inhibitor and DCCB allows neutralizing of antiregulatory mechanisms reducing drug efficacy. Results of clinical trails which promoted of the fixed combination of lisinopril (10 mg) and amlodipine (5 mg) are presented. Safety and organoprotective properties of this combination are also shown according to the trail results.